Pengaruh Aklimatisasi Lumpur Aktif terhadap Limbah Cair dari Pabrik Pangan - Nur Afiah; Muh. Rapi; Jamilah Jamilah (Bioscientist : Jurnal Ilmiah Biologi, 2022)
This study aims to: 1) Determine the effect of active sludge on reducing pollutant levels in liquid waste; 2) Knowing the combination of activated sludge and liquid waste in order to reduce environmental pollution. The type of research used is True Experimental Design research using a completely randomized design (CRD). This study consisted of 4 treatments with 5 repetitions so that there were 20 units. The first treatment was used as a control containing 100% liquid waste from food factories, the second treatment used 10 grams of activated sludge and 500 ml of food factory liquid waste, the third treatment used 10 grams of activated sludge and 600 ml of food factory liquid waste, and the fourth treatment used 10 grams activated sludge and 700 ml of food waste. The results showed that the process of acclimatization of activated sludge to liquid food waste had an effect on reducing pollutant levels of liquid food waste, as seen from the decrease in TSS (Total Suspended Solid) from 3.68 mg⁄L to 1.34 mg⁄L in treatment A, 1.3 mg⁄L treatment B, 1.32 mg⁄L in treatment C, COD (Chemical Oxygen Demand) from 32.16 mg⁄L decreased to 8.32 mg⁄L in treatment A, 11.84 mg⁄L in treatment B, and 9.28 mg⁄L in treatment C, and BOD (Biochemical Oxygen Demand) from 16.14 mg⁄L decreased to 4.12 mg⁄L in treatment A, 5.7 mg⁄L in treatment B , and 5.4 mg⁄L in treatment C and the effect of activated sludge treatment on liquid waste was evident that treatment A (10 grams of activated sludge and 500 ml of food liquid waste) had a significant effect on reducing pollutant levels from food factory wastewater.